Application of spent Agaricus subrufescens compost in integrated production of seedlings and plants of tomato - Lopes, Raul Xavier; Zied, Diego Cunha [UNESP]; Martos, Emerson Tokuda; de Souza, Rovilson José; da Silva, Romildo; Dias, Eustáquio Souza (Springer Nature, 2015)
Purpose: Spent mushroom compost (SMC) is a major solid waste product of the mushroom industry and is the material which remains at the end of a mushroom crop. Methods: Different proportions of the SMC from Agaricus subrufescens cultivation were tested to produce seedlings and plants of tomato. A commercial substrate was used, both as a control and in combination with the spent compost in different proportions. So two experiments were carried out, the first was the production and evaluation of tomato seedlings and the second was tomato cultivation from seedlings produced in the first experiment. Results: The use of different proportions of spent A. subrufescens compost resulted in a decreasing trend of all the parameters in the production of the tomato seedlings. However, in tomato cultivation for all periods of harvest, a positive effect was observed in fruiting when the seedlings were produced with spent A. subrufescens compost in comparison to the commercial control. Conclusion: It was concluded that the use of spent A. subrufescens compost for seedling production led to a higher total tomato production compared to previously reported production levels in organic cultivation systems with green, organic and other types of fertilization. These results demonstrated the great potential of spent A. subrufescens compost for use in organic tomato production because of the better quality of harvested fruit.
Keywords: Agaricus blazei; Almond mushroom; Reuse of compost; Waste